Mainstreaming Out of School Children with Community Support : A Success Story - Tripathy, Kamala Kanta (INDIAN EDUCATIONAL REVIEW, 2017)
The persistence of poverty is the most complex problem in India. One –third of the world’s 1.2 billion extremely poor are living in India. They are leading a miserable life. Education is the only weapon to eradicate poverty. But India has not been able to achieve quality elementary education. Of the factors blocking the achievement of quality elementary education for all, a high dropout rate of students is significant one. The present dropout rate at the primary level is 18 per cent. This study was undertaken to address this issue in the States of Uttarakhand and West Bengal. Out of school children in the age group 6–14 were identified and admitted into school with the support of community leaders in each village. The outcomes of the study were that 192 (112 boys and 85 girls) out of school children were admitted into schools in class appropriate to their age in both the states. An attempt was also made to bring about a change in the mindset of the stakeholders through awareness meetings regarding need and importance of quality education for all and evil consequences of child labour. An analysis of their response in the post test revealed that there was a substantial change in the mind-set of stakeholders regarding need of education for each child.